2009
DOI: 10.13033/isahp.y2009.092
|View full text |Cite
|
Sign up to set email alerts
|

Using ANP for the Selection of Green Supply Chain Management Strategies

Abstract: This study aims to designate the appropriate green supply chain management (GSCM) strategies for electronic industries to control their business functions and activities effectively. Because many previous works mixed up green strategies, regulations, and activities, we propose an integrated network model from the aspect of product development so that four business functions, i.e., design, purchasing, manufacturing, and marketing, and their activities can be identified. These functions and activities under stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Green supply chain is conceived by different research workers from four different perspectives, namely, (a) 'Green supply chain refers to the way in which innovations in SCM and industrial purchasing may be considered in the context of the environment' (Chen, Shih, Wu & Spyur, 2008); (b) Environmental SCM consists of the purchasing function's involvement in activities which include reduction, recycling, reuse and the substitution of materials (Harris & Naim, 2006); (c) 'The practice of monitoring and improving environmental performance in the supply chain…' (Nones, Morques & Evgenio, 2004); (d) 'Integrating environmental thinking into a SCM, including product design, material resourcing and selection, manufacturing processes, delivery of the final product to the consumer as well as end-of-life management of the product after its useful life' (de Brito & Vander Laan, 2010). From these four definitions, we see that there is a range of author focus and purpose on green supply chains and their management, that is, purchasing, operations, marketing or logistics, etc., also influences the definition.…”
Section: Asia-pacific Journal Of Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Green supply chain is conceived by different research workers from four different perspectives, namely, (a) 'Green supply chain refers to the way in which innovations in SCM and industrial purchasing may be considered in the context of the environment' (Chen, Shih, Wu & Spyur, 2008); (b) Environmental SCM consists of the purchasing function's involvement in activities which include reduction, recycling, reuse and the substitution of materials (Harris & Naim, 2006); (c) 'The practice of monitoring and improving environmental performance in the supply chain…' (Nones, Morques & Evgenio, 2004); (d) 'Integrating environmental thinking into a SCM, including product design, material resourcing and selection, manufacturing processes, delivery of the final product to the consumer as well as end-of-life management of the product after its useful life' (de Brito & Vander Laan, 2010). From these four definitions, we see that there is a range of author focus and purpose on green supply chains and their management, that is, purchasing, operations, marketing or logistics, etc., also influences the definition.…”
Section: Asia-pacific Journal Of Managementmentioning
confidence: 99%
“…Porter (1991) suggested that enterprises through environmental regulations to the business environment innovative technologies, in addition to regulatory compliance requirements, can further reduce production costs and increase economic efficiency. Chen et al (2008) pointed out that green innovation has a related impact on the enterprise's competitive edge.…”
Section: Green Innovations and Sustainability Issues Of Gscmmentioning
confidence: 99%